PENGARUH CERITA FABEL DIGITAL TERHADAP SIKAP KESADARAN LINGKUNGAN SISWA PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Yasmin, Elza Alida; Sunaengsih, Cucun; Amelia Karlina, Dety (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study addresses the issue of low environmental awareness among elementary school students, which affects the integrity of the relationship between humans and nature. The objective is to utilize the influence of digital fable stories as a learning media in the IPAS subject to develop environmental awareness in children aged 7-12 years, who are in Piaget’s concrete operational cognitive development stage. The research methodology employs a quantitative approach with a quasi-experimental design. The learning approach uses the digital fable